2015
DOI: 10.4265/bio.20.179
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Antimicrobial Resistance in <i>Campylobacter</i> Strains Isolated from Poultry at a Slaughterhouse and Supermarkets in Japan

Abstract: Fifty strains of Campylobacter jejuni/coli were detected in 108 specimens of chicken meat and organs sampled at six supermarkets and one poultry slaughterhouse (large scale) between April and October 2013 (isolation rates: 84.8% from the slaughterhouse, 29.3% from the supermarkets). 46/50 strains were successfully recovered and subjected to the E-test to examine their susceptibility to three fluoroquinolone antibacterial agents authorized for use in poultry in Japan: enrofloxacin (ERFX), ofloxacin (OFLX), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…The separation rate of Campylobacter spp. from the slaughterhouse reached a low point of 14.2% in this study, compared with previous reports from white-feathered broiler or turkey slaughterhouse ranging from 26.3 to 100% in China and some other Asian and African countries ( Chen et al, 2010 ; Ma et al, 2014 ; Messad et al, 2014 ; Kojima et al, 2015 ; Han et al, 2016 ). The low separation rate that was obtained may be due to undivided slaughter with the use of disinfectants to reduce the level of cross-contamination or the sample collection methods, seasonal factors ( Zendehbad et al, 2015 ), and the strict biosecurity measures used by the slaughterhouse ( Sasaki et al, 2014 ), may also account for their viable but non-culturable (VBNC) state.…”
Section: Discussioncontrasting
confidence: 56%
“…The separation rate of Campylobacter spp. from the slaughterhouse reached a low point of 14.2% in this study, compared with previous reports from white-feathered broiler or turkey slaughterhouse ranging from 26.3 to 100% in China and some other Asian and African countries ( Chen et al, 2010 ; Ma et al, 2014 ; Messad et al, 2014 ; Kojima et al, 2015 ; Han et al, 2016 ). The low separation rate that was obtained may be due to undivided slaughter with the use of disinfectants to reduce the level of cross-contamination or the sample collection methods, seasonal factors ( Zendehbad et al, 2015 ), and the strict biosecurity measures used by the slaughterhouse ( Sasaki et al, 2014 ), may also account for their viable but non-culturable (VBNC) state.…”
Section: Discussioncontrasting
confidence: 56%
“…A controversial avenue for the introduction of antibiotic-resistant Campylobacter strains to humans is through the consumption of meat, including poultry (Thakur et al, 2010; Barton, 2014; US Food and Drug Administration, 2014; Mäesaar et al, 2016). Campylobacter is present as a commensal organism in the gastrointestinal tracts (GITs) of poultry and can be antibiotic resistant (Zhao et al, 2010; Kojima et al, 2015; Ohishi et al, 2017; Raeisi et al, 2017). A Polish study indicated that as many as 94.4% of Campylobacter jejuni isolated from chicken are resistant to at least one class of antibiotic (Wieczorek et al, 2017).…”
Section: The Importance Of Antibiotic-resistant Campylobactermentioning
confidence: 99%
“…Outbreaks of food-borne diseases have been increasingly linked to raw and minimally processed fruits and vegetables; the number of reports examining the attachment of bacterial cells to food has also been growing Kim et al, 2015;Kojima et al, 2015;Kroupitski et al, 2009;Moon et al, 2007;Saggers et al, 2008. Takeuchi et al 2000 evaluated the attachment of Escherichia coli O157:H7, Listeria monocytogenes, Salmonella enterica subsp.…”
Section: Introductionmentioning
confidence: 99%